THE CONCEPT OF WASAṬIYYAH IN FIQH MUHAMMADIYAH PERSPECTIVE - Tasnim Rahman Fitra; Devrian Ali Putra; Sukma Nada Desmanto (Asy-Syari'ah, 2022)
This study discusses the concept of wasaṭiyyah Muhammadiyah's perspective onfiqh problem development, especially in Indonesia. It is related to the internal conflicts of Muslims in various aspects of life, including Islamic law or fiqh. These disputes are caused by the friction between the two opposing ideologies in methodology and approach, sometimes caused by an intervention born through contradiction between liberals who want to free themselves from the shackles of textual understanding from the conservative group. In this case, Muhammadiyah occurs to introduce itself as an organization that seeks to offer concrete solutions through its wasaṭiyyah understanding. This study aims to reveal the concept of wasaṭiyyah in Muhammadiyah fiqh, which is related to the expression of the wasaṭiyyahidea in the fiqh produced by Muhammadiyah. This study uses a literature research method that focuses on wasaṭiyyah concepts as seen from the understanding of Muhammadiyah fiqh through decisions, congress results or the other fiqh products officially issued by Muhammadiyah. This study concludes that the concept of fiqh wasaṭiyyah Muhammadiyah tries to understand and place text and context proportionally toraise non-radical characteristics and also non-liberal. Furthermore, Muhammadiyah upholds the principle of tawāsuṭwhich is combined with the codes of tawāzunand ta'ādulthrough an “Islam Berkemajuan" or the progressive Islam orientation